Method for high-valued preparation of titanium dioxide from polyolefin catalyst waste
By hydrolysis treatment under controllable pH conditions, the impurities and stability problems of polyolefin catalyst waste in the production of anatase phase TiO2 are solved, and the preparation of high-purity anatase type titanium dioxide is realized, which improves the activity of the catalyst and reduces the cost of solid waste disposal.
Patent Information
- Application Number
- CN202411726712.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art has impurity problems when producing anatase phase TiO2, and polyolefin catalyst waste is difficult to deal with and is prone to adverse phase change, which affects the stability of the preparation process and the activity of the product.
By hydrolysis treatment under controllable pH conditions and pH buffer control using bicarbonate, stable hydrolysis of polyolefin catalyst waste is achieved, and high-purity anatase titanium dioxide is prepared.
The preparation of high-purity anatase titanium dioxide has been realized, which improves the activity of the catalyst, reduces the cost of solid waste disposal, and provides a new solution to the disposal and high-value of solid waste in the petrochemical field.
Smart Images

Figure CN119528215A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing titanium dioxide by utilizing waste materials. Background Art
[0002] Polyolefins are important plastic materials, widely used in packaging, construction, automobiles and other fields. Catalysts used in the production of polyolefins, such as titanium tetrachloride (TiCl4) catalysts, are easily hydrolyzed. A little water will hydrolyze them into chloroalkoxytitanium, which is a hazardous waste and difficult to dispose of. The treatment of these catalysts needs to be studied and resolved urgently. Anatase titanium dioxide, as an important inorganic raw material, is mainly used in coatings, plastics, rubber and other industries. With the continuous growth of its demand, its market value is also continuing to rise, especially in the application of denitrification (SCR) catalysts, anatase titanium dioxide is used as an important catalyst carrier. If a new way to prepare anatase titanium dioxide with high value can be developed, it will have important economic and environmental significance.
[0003] In the market, the sulfuric acid method is generally used to produce anatase TiO2, which has a relatively low cost, but contains more impurities. One obvious impurity is sulfate residue. If the sulfate residue is not controlled well, it is easy to cause the performance of the carrier to decline. A large amount of catalyst waste is generated every year in the process of polyolefin production, including wastes such as TiCl4 and chloroalkoxy titanium. TiCl4 and chloroalkoxy titanium show high instability when in contact with water, and are prone to hydrolysis reactions, generating by-products accompanied by violent heat release, which makes process control difficult; at the same time, the particle size distribution of the produced titanium dioxide is difficult to stably control, and it is easy to generate uneven particles during the preparation process, thereby affecting its catalytic and physical properties. In addition, driven by thermodynamics and kinetics, these wastes are easy to transform into a more thermodynamically stable rutile phase under certain conditions, and the rutile phase usually does not have the high activity and characteristics required for the anatase phase. This phase change phenomenon further increases the difficulty of regulating the properties of the product during the preparation process. Therefore, how to achieve stability control of polyolefin catalyst waste during hydrolysis and effectively inhibit adverse phase changes remains a key challenge faced in current research. Summary of the invention
[0004] The present invention aims to solve the technical problems that a lot of impurities are generated when producing anatase phase TiO2 by the sulfuric acid method and the polyolefin catalyst waste is hazardous waste and difficult to dispose of, and to provide a method for preparing titanium dioxide with high value from polyolefin catalyst waste.
[0005] The method for preparing titanium dioxide from polyolefin catalyst waste is carried out according to the following steps:
[0006] 1. Prepare a hydrolysis solution and adjust the pH of the hydrolysis solution to 7-11;
[0007] 2. Slowly add the polyolefin catalyst solution waste to the hydrolysis solution in step 1 and stir thoroughly;
[0008] 3. Separate the solid from the liquid and retain the solid part;
[0009] 4. Naturally dry the solid obtained above to obtain anatase titanium dioxide.
[0010] The method for preparing titanium dioxide from polyolefin catalyst waste can also be carried out according to the following steps:
[0011] 1. Add ammonia solution to the polyolefin catalyst solution waste until the pH is 7 and stir thoroughly;
[0012] 2. Separate the solid from the liquid and retain the solid part;
[0013] 3. Naturally dry the solid obtained above to obtain anatase titanium dioxide.
[0014] The main components of the polyolefin catalyst solution waste in the present invention are TiCl4 and chloroalkoxytitanium.
[0015] The present invention utilizes polyolefin catalyst waste to hydrolyze under controllable pH conditions, and can hydrolyze the waste to synthesize anatase titanium dioxide. The activity of the SCR catalyst prepared from the titanium dioxide prepared by this method is even slightly better than that of the catalyst prepared from the traditional sulfuric acid method titanium dioxide, thereby realizing the resource utilization of waste and reducing the cost of catalyst preparation. The method of the present invention also determines that the key to controlling the hydrolysis of polyolefin catalyst waste lies in pH by analyzing the microstructural differences between rutile and anatase. When the pH is too low, a rutile phase with poor activity is easily produced, while when the pH is too high, the hydrolysis is too violent. Using bicarbonate for pH buffering control can mildly hydrolyze the waste to produce anatase titanium dioxide. The method of the present invention also reveals that the key to the control mechanism of the hydrolysis of polyolefin catalyst waste lies in the influence of pH on Ti(H2O) y (OH) x (4-x)+ The ligand structure further affects the degree of dehydration condensation of the hydrolysis center during hydrolysis, which is the fundamental factor controlling the structure of the resulting phase.
[0016] The present invention utilizes the hydrolysis of polyolefin catalyst titanium mixed waste under controllable buffer conditions to realize the conversion of polyolefin catalyst titanium mixed waste into high-purity solid phase anatase titanium dioxide, which not only provides a new solution for the disposal and high-value of solid waste in the petrochemical field, but also provides support for the reduction of production costs of catalysts in downstream markets such as flue gas denitrification. The key to controlling the hydrolysis of polyolefin catalyst titanium mixed waste in the method of the present invention is to regulate Ti to Ti(H2O) y (OH) x (4-x)+The ionic form is slowly and directional hydrolyzed, and the controllable synthesis of rutile phase and anatase phase is achieved based on different hydrolysis conditions of H2O ligand (acidic) and OH ligand (alkaline).
[0017] Technical effects of the present invention:
[0018] 1. The present invention can produce high-purity anatase titanium dioxide under controllable buffer conditions, with a purity of 99.5wt%;
[0019] 2. The present invention can utilize catalyst titanium slag waste as a resource, provide a new way to reduce solid waste disposal, and reduce the cost of preparing flue gas denitrification catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of titanium dioxide samples obtained in experiments 1 to 6;
[0021] Figure 2 XRD diagrams of titanium dioxide samples obtained in Experiment 1 and Comparative Experiment 4;
[0022] Figure 3 This is a data chart showing the NO conversion rate tested in the NH3-SCR activity test system in Experiment 8. DETAILED DESCRIPTION
[0023] Specific implementation method 1: This implementation method is a method for preparing titanium dioxide from polyolefin catalyst waste with high value, which is specifically carried out according to the following steps:
[0024] 1. Prepare a hydrolysis solution and adjust the pH of the hydrolysis solution to 7-11;
[0025] 2. Slowly add the polyolefin catalyst solution waste to the hydrolysis solution in step 1 and stir thoroughly;
[0026] 3. Separate the solid from the liquid and retain the solid part;
[0027] 4. Naturally dry the solid obtained above to obtain anatase titanium dioxide.
[0028] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the hydrolysis solution in step 1 is NH4HCO3 aqueous solution, glacial acetic acid or (NH4)2CO3 aqueous solution. Others are the same as specific embodiment 1.
[0029] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the concentrations of the NH4HCO3 aqueous solution and the (NH4)2CO3 aqueous solution are both 0.1 mol / L to 10 mol / L. Other aspects are the same as specific implementation method 1 or 2.
[0030] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the polyolefin catalyst solution waste in step 2 includes TiCl4 and chloroalkoxytitanium. The rest is the same as specific embodiments 1 to 3.
[0031] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that the stirring time in step 2 is 0.1h to 5h. The rest is the same as specific embodiment 4.
[0032] Specific embodiment 6: This embodiment is different from specific embodiment 5 in that the solid-liquid separation in step 3 is a combination of one or more methods of centrifugal washing and / or filtration washing and / or reflux washing. The rest is the same as specific embodiment 5.
[0033] Specific embodiment 7: This embodiment is a method for preparing titanium dioxide from polyolefin catalyst waste with high value, which is specifically carried out according to the following steps:
[0034] 1. Add ammonia solution to the polyolefin catalyst solution waste until the pH is 7 and stir thoroughly;
[0035] 2. Separate the solid from the liquid and retain the solid part;
[0036] 3. Naturally dry the solid obtained above to obtain anatase titanium dioxide.
[0037] Specific embodiment eight: This embodiment differs from specific embodiment seven in that the polyolefin catalyst solution waste in step one includes TiCl4 and chloroalkoxytitanium. The rest is the same as specific embodiment seven.
[0038] Specific embodiment 9: This embodiment is different from specific embodiment 8 in that the mass concentration of the ammonia solution in step 1 is 25% to 28%. Other aspects are the same as specific embodiment 8.
[0039] Specific embodiment 10: This embodiment is different from specific embodiment 9 in that the stirring time in step 1 is 0.1h to 5h. The rest is the same as specific embodiment 9.
[0040] The present invention is verified by the following tests:
[0041] Experiment 1: This experiment is a method for preparing titanium dioxide from polyolefin catalyst waste, which is specifically carried out in the following steps:
[0042] 1. Prepare 100mL of 2mol / L NH4HCO3 hydrolysis solution and test its pH to 7.8;
[0043] 2. Slowly add 2.5 mL of polyolefin catalyst solution waste to the hydrolysis solution in step 1 and stir thoroughly for 0.5 h;
[0044] The main components of the polyolefin catalyst solution waste are TiCl4 and chloroalkoxytitanium;
[0045] 3. Centrifuge and retain the solid part;
[0046] 4. Naturally dry the solid obtained above to obtain titanium dioxide.
[0047] Experiment 2: This experiment is a method for preparing titanium dioxide from polyolefin catalyst waste, which is specifically carried out in the following steps:
[0048] 1. Add ammonia solution to the polyolefin catalyst solution waste until the pH is 7 and stir thoroughly;
[0049] The mass concentration of the ammonia solution is 25% to 28%;
[0050] The main components of the polyolefin catalyst solution waste are TiCl4 and chloroalkoxytitanium;
[0051] 2. Centrifuge and retain the solid part;
[0052] 3. Naturally dry the solid obtained above to obtain titanium dioxide.
[0053] Experiment 3: This experiment is different from Experiment 1 in that: in step 1, 100 mL of 1 mol / L (NH4)2CO3 hydrolysis solution was prepared and its pH was tested to be 9.2. The rest is the same as Experiment 1.
[0054] Experiment 4: This experiment differs from Experiment 1 in that in step 1, 100 mL of 1 mol / L (NH4)2CO3 hydrolysis solution was prepared and concentrated ammonia was added to adjust the pH to 10. The rest was the same as Experiment 1.
[0055] Experiment 5: Prepare 100 mL of 1 mol / L (NH4)2CO3 hydrolysis solution in step 1, add concentrated ammonia water to adjust the pH to 11. The rest is the same as experiment 1.
[0056] Experiment 6: In step 1, 5.5 mL of glacial acetic acid was added to 85 mL of H2O, and concentrated ammonia was added to adjust the pH to 10 to obtain a hydrolysis solution. The rest was the same as in experiment 1.
[0057] The XRD characterization results of the titanium dioxide samples obtained in the above six experiments are as follows: Figure 1As shown, the green curve corresponds to test one, the blue curve corresponds to test two, the red curve corresponds to test three, the purple curve corresponds to test four, the orange curve corresponds to test five, and the brown curve corresponds to test six. The TiO2 content, particle size and crystal form information are shown in Table 1. It can be seen that the products are all rutile TiO2 with uniform particle size and high purity.
[0058] Table 1
[0059]
[0060] Comparative Test 1: This test is a method for preparing titanium dioxide from polyolefin catalyst waste, which is specifically carried out in the following steps:
[0061] 1. Prepare 100 mL of hydrolysis solution, the formula of which is 2 mol / L NH4HCO3;
[0062] 2. Add glacial acetic acid to the above hydrolysis solution to adjust the pH to 5;
[0063] 3. Slowly add 2.5 mL of polyolefin catalyst solution waste;
[0064] The main components of the polyolefin catalyst solution waste are TiCl4 and chloroalkoxytitanium;
[0065] 4. Stir the obtained mixture thoroughly for 0.5 h;
[0066] 5. After stirring, centrifuge to separate the solids;
[0067] 6. Naturally dry the solid obtained above to obtain titanium dioxide.
[0068] Comparative Experiment 2: This experiment differs from Comparative Experiment 1 in that hydrochloric acid is added in step 2 to adjust the pH to 3. The rest is the same as Comparative Experiment 1.
[0069] The amount of precipitate obtained in step 4 of comparative experiment 1 was too small, and no precipitate was produced in step 4 of comparative experiment 2, and both could not be recovered.
[0070] Comparative Experiment 3: This experiment differs from Comparative Experiment 1 in that concentrated ammonia water is added in step 2 to adjust the pH to 12. The rest is the same as Comparative Experiment 1. In step 3 of Comparative Experiment 3, the hydrolysis is too intense, the liquid splashes, and cannot be recovered.
[0071] Comparative Test 4: The difference between this test and Test 1 is that the titanium dioxide obtained in Test 1 was calcined at 600℃ for 2h. The rest is the same as Test 1. The crystal form of the titanium dioxide after calcination in Comparative Test 4 is rutile, such as Figure 2 As shown, the red curve is the titanium dioxide obtained in comparative experiment four, and the blue curve is the titanium dioxide obtained in experiment one.
[0072] Experiment 7: The titanium dioxide obtained in Experiment 1 was calcined at 450°C for 2h.
[0073] Experiment 8: The titanium dioxide obtained in Experiment 1 and the titanium dioxide obtained after calcination in Experiment 7 were used to prepare SCR catalyst: 4.795g of rutile titanium dioxide (the titanium dioxide obtained in Experiment 1, the titanium dioxide obtained after calcination in Experiment 7 and the titanium dioxide prepared by the sulfuric acid method were tested and compared respectively) was added to 50mL of H2O and stirred thoroughly to obtain a first solution; 0.0708g of NH4VO3 and 0.1594g of ammonium metatungstate were added to 50mL of H2O, heated and stirred at 80°C until completely dissolved, cooled and continued to stir to obtain a second solution; the second solution was transferred to the first solution, magnetically stirred, the temperature was raised to close to the boiling point but not boiling, and stirring was continued until it was completely dried and became a solid powder; the sample was recovered and dried at 80°C; the powder was then calcined at 550°C for 4h, with a heating rate of 10°C / min.
[0074] The three catalysts synthesized above were placed in the NH3-SCR activity test system to test their NO conversion rates. Figure 3 As shown, the red curve corresponds to experiment 1, the green curve corresponds to experiment 7, and the blue curve corresponds to the titanium dioxide prepared by the sulfuric acid method. The results show that the SCR catalyst prepared by using the anatase titanium dioxide (red curve) obtained by hydrolysis without calcination in experiment 1 is equivalent to the fresh SCR catalyst prepared by the sulfuric acid method titanium dioxide (blue curve), and even slightly better than the latter in the low temperature range (150-350℃).
Claims
1. A method for preparing titanium dioxide from polyolefin catalyst waste, characterized in that The method for preparing titanium dioxide from polyolefin catalyst waste is carried out according to the following steps:
1. Prepare a hydrolysis solution and adjust the pH of the hydrolysis solution to 7-11; 2. Slowly add the polyolefin catalyst solution waste to the hydrolysis solution in step 1 and stir thoroughly; 3. Separate the solid from the liquid and retain the solid part; 4. Naturally dry the solid obtained above to obtain anatase titanium dioxide.
2. The method for preparing titanium dioxide from polyolefin catalyst waste according to claim 1, characterized in that The hydrolysis solution described in step 1 is NH4HCO3 aqueous solution, glacial acetic acid or (NH4)2CO3 aqueous solution.
3. The method for preparing titanium dioxide from polyolefin catalyst waste according to claim 2, characterized in that The concentrations of the NH4HCO3 aqueous solution and the (NH4)2CO3 aqueous solution are both 0.1 mol / L to 10 mol / L.
4. The method for preparing titanium dioxide from polyolefin catalyst waste according to claim 1, characterized in that The polyolefin catalyst solution waste in step 2 includes TiCl4 and chloroalkoxytitanium.
5. The method for preparing titanium dioxide from polyolefin catalyst waste according to claim 1, characterized in that The stirring time in step 2 is 0.1h to 5h.
6. The method for preparing titanium dioxide from polyolefin catalyst waste according to claim 1, characterized in that The solid-liquid separation in step three is a combination of one or more methods of centrifugal washing and / or filtration washing and / or reflux washing.
7. A method for preparing titanium dioxide from polyolefin catalyst waste, characterized in that The method for preparing titanium dioxide from polyolefin catalyst waste is carried out according to the following steps:
1. Add ammonia solution to the polyolefin catalyst solution waste until the pH is 7 and stir thoroughly; 2. Separate the solid from the liquid and retain the solid part; 3. Naturally dry the solid obtained above to obtain anatase titanium dioxide.
8. The method for preparing titanium dioxide from polyolefin catalyst waste according to claim 7, characterized in that The polyolefin catalyst solution waste described in step 1 includes TiCl4 and chloroalkoxytitanium.
9. The method for preparing titanium dioxide from polyolefin catalyst waste according to claim 7, characterized in that The mass concentration of the ammonia solution described in step 1 is 25% to 28%.
10. The method for preparing titanium dioxide by high-value polyolefin catalyst waste according to claim 7, characterized in that The stirring time in step 1 is 0.1h to 5h.